PENGELOLAAN OBJEK WISATA CAGAR ALAM RIMBO PANTI KABUPATEN PASAMAN - Afrida, Yelni; Chair, Ira Meirina; Kasmita, Kasmita (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2015)
This study aims to determine the management Attractions Rimbo PantiNature Reserve Pasaman. This type of research is descriptive qualitative andquantitative research (mixed method). This study consists of four indicators,namely management: Planning is focused on the preservation and protection offlora and fauna. Organizing managers led by a Head of Tourism. The briefing is toinvite and communicate to all members to create a positive impression ofattractions. Supervision is done by janitors and security in the attraction. Thequestionnaire results travelers and tourists say less well choose not to come backto attractions with a percentage of 57%. Suggestions rating for the manager is topay more attention again in pengelolaaan attraction especially in tourist facilities.Key Words: Planning, Organizing, Directing, Actuating